Evaluation of Physical Parameter Environment in the Hemodialysis Unit Based on Hospital Environmental Health Standards - Ukik Agustina; Adelia Rahma Fadila; Vina Febrianita; Veinadaracantika Nur Anwar; Viola Az Zahra; Juniar Ayu Langen Sari (Griya Eka Sejahtera, 2026)
Background:The physical environmental quality of a hemodialysis unit plays an important role in supporting safe and comfortable healthcare services, as well as preventing and controlling infections. This study aimed to evaluate the physical environmental parameters of the hemodialysis unit based on the Environmental Health Quality Standards (SBMKL), in accordance with Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2023.Methods: This study employed a quantitative descriptive design to evaluate the physical environmental conditions of the treatment and isolation rooms in the hemodialysis unit. The parameters measured included air temperature, relative humidity, lighting, noise levels, Air Changes per Hour (ACH), and air pressure using calibrated instruments. The data were analyzed descriptively by comparing the measurement results with the Environmental Health Quality Standards (SBMKL).Results: The results showed that the mean air temperatures in the treatment and isolation rooms were 26.3°C and 26.5°C, respectively; relative humidity was 61.1% and 59.3%; lighting intensity was 262.8 lux and 273.2 lux; noise levels were 63.4 dB and 58.0 dB; Air Changes per Hour (ACH) were 21.6 and 19.5 times/hour; and air pressure was 1.5 Pa in both rooms. The lighting and ACH parameters met the applicable standards at all measurement points (100%), whereas air pressure did not meet the standard at any measurement point (0%). Relative humidity and noise levels showed higher compliance in the isolation room than in the treatment room. However, air temperature did not meet the applicable standards in either room.Conclusion: Based on results the concluded that quality environment physical hemodialysis unit Not yet fully fulfill SBMKL. Evaluation integrated all physical parameters required as indicator performance HVAC system for support quality service, prevention infection, and safety patient.